Variation and significance of serum microRNA-21 level in pediatric pulmonary artery hypertension associated with congenital heart disease - Shen, Yanming; Liao, Dongshan; Shangguan, Wenlin; Chen, Liangwan (Frontiers in Cardiovascular Medicine, 2024)
Objective This study strives to the variation and significance of microRNA-21 (miR-21) in children with congenital heart disease (CHD)-related pulmonary artery hypertension (PAH). Methods Children with CHD (n = 179) were selected as subjects, including 101 children without PAH and 78 children with PAH. All children underwent general data collection, laboratory examination, echocardiography and cardiac catheterization. After detection of serum miR-21 expression, the predictive value and the impacts of serum miR-21 for PAH and postoperative critical illness were analyzed. Results Serum creatine kinase isoenzyme (CK-MB), B-type natriuretic peptide (BNP) and miR-21 were elevated, but ejection fraction (EF) and cardiac index (CI) were decreased in the CHD-PAH group. Serum miR-21 assisted in predicting PAH in CHD children, with the area under curve (AUC) of 0.801 (95% CI of 0.735∼0.857), a cut-off value of 2.56, sensitivity of 73.08, and specificity of 72.28%. Serum miR-21 in children with CHD-PAH was correlated with clinicopathological indicators such as systolic pulmonary artery pressure, mean pulmonary arterial pressure, BNP and CI. Serum miR-21 helped predict the development of postoperative critical illness in children with CHD-PAH, with an AUC of 0.859 (95% CI: 0.762–0.927, cut-off value: 4.55, sensitivity: 69.57%, specificity: 92.73%). Increased serum miR-21 was an independent risk factor of postoperative critical illness in children with CHD-PAH. Conclusion Serum miR-21 was upregulated in children with CHD-PAH, which may serve as a predictive biomarker for the onset of PAH and postoperative critical illness in CHD children.